THE ROLE OF DIGITAL TECHNOLOGY IN TEACHING ENGLISH LANGUAGE - Nurullayeva , Bahora; Olimova , Zuhro; Azimjonovna , Zaynab (Educational Research in Universal Sciences, 2023)
The use of information technology in English language instruction is covered in the first section of this essay. These days, language acquiring more must for all language is simple feat. Many people consider shift in teaching philosophy towards 1800s A variety of techniques emerged, including the direct method, the audio-lingual method,the grammar translation method, and others. Although many students in industrialized nations and among educational elites abroad are increasingly familiar with the Internet and its websites, it nevertheless holds little importance for a great number of people who lack the most fundamental tools for survival.